2021
DOI: 10.1053/j.ajkd.2021.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor Stabilization as an Emerging Therapy for CKD-Related Anemia: Report From a Scientific Workshop Sponsored by the National Kidney Foundation

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…Daprodustat was effective in maintaining Hb concentrations in a subgroup of patients with an unplanned dialysis start, in patients receiving PD, and in patients with inflammation. The safety profile was similar between treatment groups in this 52-week study; the scientific and medical communities are still waiting for long-term safety data and recommend additional studies . Based on the efficacy and short-term safety data in this study, daprodustat may represent a potential oral alternative to one of the conventional ESAs for patients with CKD who are starting dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Daprodustat was effective in maintaining Hb concentrations in a subgroup of patients with an unplanned dialysis start, in patients receiving PD, and in patients with inflammation. The safety profile was similar between treatment groups in this 52-week study; the scientific and medical communities are still waiting for long-term safety data and recommend additional studies . Based on the efficacy and short-term safety data in this study, daprodustat may represent a potential oral alternative to one of the conventional ESAs for patients with CKD who are starting dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their mode of action in upregulating a large number of transcriptional targets, there have been quite a number of theoretical concerns about this new class of drugs. These include, but are not limited to, increased angiogenesis and vascular endothelial growth factor (VEGF) production, worsening diabetic retinopathy, increased cancer risk, worsening renal progression due to kidney fibrosis, exacerbation of pulmonary arterial hypertension, increased infection risk, and enhanced progression of polycystic kidney disease [19 ▪ ]. Most of these concerns have not been adequately addressed in the phase 3 studies, particularly the cancer risk due to the relatively short follow-up period of 1–2 years.…”
Section: Safety Concernsmentioning
confidence: 99%
“…Preclinical data have shown positive effects of HIF-PH inhibition on genes involved in iron transport and availability, including upregulation of divalent metal transporter-1 and duodenal cytochrome b (potentially improving iron absorption from the gut), as well as transferrin and the transferrin receptor (improving iron availability to the bone marrow) [19 ▪ ]. One of the early phase 2 trials of roxadustat found that dialysis patients randomized to roxadustat plus oral iron had a similar hemoglobin response to patients randomized to roxadustat and intravenous iron [20], and this was thought to be due to indirect downregulation of hepcidin improving oral iron absorption.…”
Section: Effect On Iron Availabilitymentioning
confidence: 99%
“…These include enzymes which affect histone methylation, RNA and DNA methylation, ribosome function, RNA splicing, and matrix formation [5]. Pleotropic effects of HIF-PHIs have been caused for concern and form the basis for cautionary statements from the Asian-Pacific Society of Nephrology [6] and US National Kidney Foundation [7] published in 2021 (Table 1). These statements were developed prior to the publication of global phase 3 trials of three HIF-PHIs which are sufficiently powered in subject number and duration to assess adverse events and long-term safety.…”
Section: Hif-phi Mechanism Of Actionmentioning
confidence: 99%